Implementation of Adaptive Physical Education at the Inclusive Organizing School in Martapura District - Hakiki, Muhammad Noor Fajri; Hidayatullah, Furqon; Umar, Fadilah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study aims to determine how far adaptive physical education is implemented in inclusive schools. This research uses descriptive qualitative research with a case study model. Collecting data using techniques The interview used is the unstructured interview and observation. The subjects of this study were school principals, adaptive physical education teachers and special mentor teachers (GPK), and children with special needs students. Data analysis used is data reduction, data display, and conclusion. The results showed that the formulation of learning objectives was clear but not by conditions such as challenges in planning and implementing adaptive physical education programs, such as limited infrastructure and lack of teacher knowledge in accommodating the needs of students with special needs. This study suggests the need to improve the quality of syllabus programs and lesson plans to meet the needs of students with special needs and for teachers to receive special training in adaptive physical education. This study also recommends providing adequate infrastructure and facilities and promoting inclusive education.